Four-year match injury surveillance in male Welsh professional Rugby Union teams. (March 2020) - Bitchell, Charlotte Leah; Mathema, Prabhat; Moore, Isabel S
Abstract: Objectives: To report match injury incidence, burden and mechanism over a four-year period in professional male Welsh Regional Rugby Union. Design: Descriptive; Longitudinal. Setting: Welsh Regional Rugby Union. Participants: Four Welsh Regional male Rugby Union teams. Main Outcome Measures: All time-loss injuries sustained between July 1, 2012 and June 30, 2016. Incidence (injuries/1000 h), severity (mean and median days lost per injury), burden (days-lost/1000 h) and proportions (%) were calculated. Results: The overall injury incidence and burden was 99.1 injuries/1000 h and 2570.3 days-lost/1000 h. Concussion represented the highest incidence and burden of all specific injuries, with increases in burden from 2012/13 (86.5 days-lost/1000 h) to 2015/16 (302.4 days-lost/1000 h). Acromio-clavicular (AC) joint injuries increased in burden from 2012/13 to 2015/16 (71.3 vs 130.6 days-lost/1000 h). However, anterior thigh haematomas decreased in incidence (8.2 vs 2.4 injuries/1000 h) and burden (48.6 vs 17.7 days lost/1000 h) across the same period. Tackle events contributed to the highest proportion of match injuries (being tackled: 20–31%, tackling: 30–42%). Conclusions: Injury incidence was higher than previously reported for professional Rugby Union. Decreases in anterior thigh haematoma and increases in concussion and AC joint injuries were shown, identifying a change in contact-related match injury risk. Highlights: Injury incidence was higher than previously reported in professional Rugby Union. The incidence and burden of concussion injuries has increased. The burden of acromio-clavicular joint injuries has increased. The incidence of anterior thigh haematoma injuries has decreased. The proportion of injuries sustained from a tackle during matches has remained high.